ACHILLES' BRUTISH HELLENISM: GREEK IDENTITY IN THE HEROIKOS - McCloskey, Benjamin (My University, 2017)
Philostratus’ Herōikos depicts two anonymous interlocutors who meet and talk. One of the two, known as the Vinedresser, spends much of their conversation informing the other, the Phoenician, about the true history of the heroes, most of which he claims to have learned from Protesilaos. Central to his account are three stories of acts of violence the revenant Achilles commits against humans. This article argues that these acts of violence may be understood as coherent and compatible manifestations of Achilles’ cultural identity, which is both violent in its defense of Greece and hostile toward Rome.
Citation: McCloskey, B. (2017). ACHILLES' BRUTISH HELLENISM: GREEK IDENTITY IN THE HEROIKOS. Classical Philology, 112(1), 63-85. Retrieved from <Go to ISI>://WOS:000392256700004
Keywords: Classics